ANALISIS GAUSSIAN DAN EDGE CONNECTION DALAM PENAJAMAN DETEKSI TEPI MENGGUNAKAN METODE CANNY - Kezia Satyawati; Junius Karel Tampubolon; R. Gunawan Santosa (Universitas Kristen Duta Wacana, 2016)
Edge detection is one of many ways to get information from an image without big data storage needed. In this research, the edge detecting is done by implementing Canny edge detection algorithm. The focus of this research is to analyze the effect of two variables of the first process of Canny, Gaussian filter smoothing, that is size of matrix and variance, to the sharpening of edge detection. The testing is done by changing the size of the matrix and the value of the variance. The results showed that the best matrix size and variance for sharp edge detection is less than 30x30 and 30.